Psychosocial determinants of oral health outcomes in young children - Kopycka-Kedzierawski, Dorota T.; Ragusa, Patricia G.; Feng, Changyong; Flint, Kim; Watson, Gene E.; Wong, Cynthia L.; Gill, Steven R.; Billings, Ronald J.; O’Connor, Thomas G. (Frontiers in Pediatrics, 2024)
Objective: To examine the social determinants of early childhood caries (ECC), one of the greatest public health risks affecting children, and examine alternative pathways of influence. Methods: A physically healthy, socio-demographically high-risk sample of initially caries-free children, aged 1-4 years, was prospectively studied for 2 years. At 6-month intervals, assessments were made of caries presence from a standard dental exam; oral microbiology was assayed from saliva samples; oral hygiene behaviors and psychological and psychosocial risk exposure were derived from interviews and questionnaires. Results: 189 children were enrolled; ECC onset occurred in 48 children over the 2-year study period. A composite measure of psychosocial risk was significantly associated with ECC onset over the course of the study (1.57, 95%CI 1.12–2.20,p<.001) and significantly associated with multiple risks for ECC, including poor diet/feeding (.92; 95%CI .22–1.61,p<.01), poor oral hygiene (.39; 95%CI .09-.68), p<.05), and higher concentrations Lactobacilli (.96; 95%CI .43–1.49,p<.001). Multivariable regression analyses provided indirect support for the hypothesis that psychosocial risk exposure predicts ECC onset via behavioral and oral hygiene pathways. Conclusions: The study provides novel evidence that psychosocial factors influence many of the purported risks for ECC and strong evidence that there are social and psychological determinants of ECC onset.